Sibu Rural District Council: Leftenan Kolonel Saiful Anwar Md Ali / Haessler Symphoon anak Paul - Paul, Haessler Symphoon (University Technology MARA Sarawak, 2014)
The whole area of Sibu Rural District Council (SRDC) lies within the Sibu Administrative Division. It measures approximately 5,869.35 square kilometres with the recent inclusion of Selangau District into SRDC jurisdiction in 2002. In the early days, ever since it’s experimental formation, the area of SRDC was divided into wards system, which originally consisted of twenty-two wards. Somehow later, due to the specific review on the demarcation of boundary, Ward 6, (the adjacent area which lies next to the border outskirt ofthe then Sibu Municipal Council) was then vested into Sibu Municipal Council (SMC) administrative jurisdiction in 1981. Similarly, Ward 1, which was commonly known as Igan area was themhanded over officially to the administrative authority of Matu-Daro District Council in October, 1991. Thus, SRDC was then reduced to only twenty wards and in comparison, the area size was approximately about 25 times larger than the present area of SMC.